Prototype temperature monitoring system for medicine refrigeration in the pharmaceutical installation - Willy Willy; Haryono Haryono; Handri Santoso; Ito Wasito (Institute of Computer Science (IOCS), 2023)
Patient safety in a hospital is a healthcare service that is safe and non-harmful to patients. All components of healthcare services (doctors, nurses, and other health teams) in hospitals must be aware of and care about patient safety while in the hospital. One of the most important components is monitoring the temperature of the medicine refrigeration. Human resources or work overload often leads to the need for more monitoring of the temperature of medicine refrigeration. Therefore, IoT technology can be the solution to assist in monitoring the temperature of the medicine refrigerator. The method used in this study is observation. Based on the conducted research, it is proven that the IOT system for temperature monitoring can reduce missed temperature records. The results of this study indicate that the DHT22 sensors have good accuracy as they remain within the accuracy range of the room thermometer used as a reference, with a temperature reading accuracy of ±1oC and a maximum temperature measurement limit of 70oC. The data collection process uses the ESP8266 as the microcontroller, which is then connected to the DHT22 module as a temperature and humidity sensor and sends a database every 30 seconds. The real-time temperature and humidity measurement results can be viewed through mobile apps using the Flutter programming language and the website. If the temperature exceeds 8oC, the fan LED will automatically turn on and send notifications to WhatsApp registered using Python and Twilio. Furthermore, the existing data can be analyzed using a machine learning model, enabling the prediction of when the refrigerator will be damaged as a preventive measure